Penanaman Nilai-nilai Akhlakul Karimah Siswa di MI Muhammadiyah Al Akbar Pandeyan (Studi Analisis Aksiologi Filsafat Islam) - Mujiburahman, Mujiburahman; Sutrisno, Agus (Lembaga Yasin AlSys, 2025)
This research uses a descriptive qualitative research approach. The aim of this research is to determine the implementation of students' moral values ​​at MIM Al Akbar Pandeyan. Data collection was carried out by observation, interviews and documentation. The data analysis and processing is taken when the researcher is in the field and after collecting data from the field. For data analysis, researchers collect data (display data) then reduce the data, present the data and then draw conclusions. From the research results, it can be concluded that the implementation of students' moral values ​​at MIM Al Akbar Pandeyan is good. After efforts to instill good morals in students, the children's attitudes have begun to change. Students begin to respect the teacher, are disciplined, honest and care about their friends. Instilling morals in students is carried out by being a role model, providing advice, habituation, and providing a deterrent effect. The factors that influence the implementation of student morals are divided into 2 supporting factors, namely IMTAQ habits which are carried out every day and cooperation between fellow teachers in developing students' morals. The inhibiting factors are students' lack of awareness of good morals, lack of attention from parents, and the community environment, especially the social environment. The solutions used by teachers to overcome obstacles in implementing students' moral values ​​include providing advice, actively maintaining good relationships with students' parents/guardians and teachers always collaborating with other teachers.